NOUNS AND NOUN GROUPS - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2022)
Definition of Noun Group and Noun A noun group is a linguistic sequence which may function as subject, object, subject complement, complement of a preposition or in a PossG structure, or as dependent element of another noun head.